Novel Drug Delivery Particles Can Provide Dual Effects on Cancer “Theranostics” in Boron Neutron Capture Therapy - Abdul Basith Fithroni; Haruki Inoue; Shengli Zhou; Taufik Fatwa Nur Hakim; Takashi Tada; Minoru Suzuki; Yoshinori Sakurai; Manabu Ishimoto; Naoyuki Yamada; Rani Sauriasari; Wolfgang A. G. Sauerwein; Kazunori Watanabe; et al. (Cells)
Boron (B) neutron capture therapy (BNCT) is a novel non-invasive targeted cancer therapy based on the nuclear capture reaction 10B (n, alpha) 7Li that enables the death of cancer cells without damaging neighboring normal cells. However, the development of clinically approved boron drugs remains challenging. We have previously reported on self-forming nanoparticles for drug delivery consisting of a biodegradable polymer, namely, “AB-type” Lactosome® nanoparticles (AB-Lac particles)- highly loaded with hydrophobic B compounds, namely o-Carborane (Carb) or 1,2-dihexyl-o-Carborane (diC6-Carb), and the latter (diC6-Carb) especially showed the “molecular glue” effect. Here we present in vivo and ex vivo studies with human pancreatic cancer (AsPC-1) cells to find therapeutically optimal formulas and the appropriate treatment conditions for these particles. The biodistribution of the particles was assessed by the tumor/normal tissue ratio (T/N) in terms of tumor/muscle (T/M) and tumor/blood (T/B) ratios using near-infrared fluorescence (NIRF) imaging with indocyanine green (ICG). The in vivo and ex vivo accumulation of B delivered by the injected AB-Lac particles in tumor lesions reached a maximum by 12 h post-injection. Irradiation studies conducted both in vitro and in vivo showed that AB-Lac particles-loaded with either 10B-Carb or 10B-diC6-Carb significantly inhibited the growth of AsPC-1 cancer cells or strongly inhibited their growth, with the latter method being significantly more effective. Surprisingly, a similar in vitro and in vivo irradiation study showed that ICG-labeled AB-Lac particles alone, i.e., without any 10B compounds, also revealed a significant inhibition. Therefore, we expect that our ICG-labeled AB-Lac particles-loaded with 10B compound(s) may be a novel and promising candidate for providing not only NIRF imaging for a practical diagnosis but also the dual therapeutic effects of induced cancer cell death, i.e., “theranostics”.